Sexual partnership according to women with the human immunodeficiency virus - Gir, Elucir; Canini, Silvia RMS; Carvalho, Milton J; Reis, Renata K; Duarte, Geraldo (Brazilian Journal of Sexually Transmitted Diseases, 2006)
Introduction: various factors influence the vulnerability of women to acquire HIV, including low perceived risk and lack of knowledge about theirsexual partners’ risk behaviors. Objective:examine how women with HIV/aids perceive risk behaviors related to acquiring the infection and to theirsexual partners. Methods:a descriptive and exploratory study was carried out at the outpatient clinic for infectious-contagious diseases and gyneco-logy of a teaching hospital in the interior of São Paulo State. We interviewed 50 women with HIV, who were under clinical follow-up during thepuerperium, using an interview script. EPI-INFO 6.0 was used for data analysis. Results:participants presented low perceived risk to acquireHIV/aids; 36 (72%) of them found out about their infection by chance and 33 (66%) informed they did not perform any risk behavior to acquire thisvirus. Forty-two women (84%) attributed their HIV infection to sexual intercourse, and most of them considered their first or second partner as thesource of infection. As to the aspects of their partners’ behavior considered as a “source of infection”, these women mentioned isolated risk factors,and 38 of them (76.0%) indicated more than one associated risk factor. Conclusion:health education programs should adopt prevention of sexualtransmission as one of their main targets, with a view to making people aware of the need to adopt safe sexual behavior. In view of the advancementof HIV/aids in the female population, specific prevention strategies need to be directed at this clientele, and men need to be made aware of their co-responsibility for the sexual and reproductive health of their partners.